Capital social, santé et minorités francophones - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Revue canadienne de santé publique / Canadian Journal of Public Health, 2006)

Social capital, health and Francophone minorities - Bouchard, Louise; Gilbert, Anne; Landry, Rodrigue; Deveau, Kenneth (Canadian Journal of Public Health / Revue canadienne de santé publique, 2006)
The goal of this article is to outline the analytical perspectives of the concept of social capital regarding health and health management. Social capital, as defined in terms of social networks and resources, has a positive impact on a number of areas, notably the health, well-being, and social and economic development of communities. It is also a useful tool for implementing social policy, especially for marginal populations, the elderly, social assistance payments, etc. An action strategy based on the support and development of networks is the key to achieving the social development, health, and well-being of populations. The social ties promoted by these networks provide people with social, cognitive, and emotional support. This has a direct impact on their self-esteem and sense of personal achievement. They also facilitate access to social resources, including social advancement opportunities. In this paper, we examine the vitality, determinants of health, and health management of Canada’s minority Francophone communities.

Les francophones de l'Ontario de 65 ans et plus : un profil statistique - Cardinal, Linda; Plante, Nathalie; Sauvé, Anik (Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa, 2006)

Rapport sommaire de l’Enquête sur les comportements à risque des jeunes adultes francophones vivant en situation linguistique minoritaire - de Moissac, Danielle; Delaquis, Stéfan; Rioux, Ginette (Collège universitaire de Saint-Boniface, 2006)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)